Sensorimotor Synchronization with Different Metrical Levels of Point-Light Dance Movements - Su, Yi-Huang (Frontiers in Human Neuroscience, 2016)
Rhythm perception and synchronization have been extensively investigated in the auditory domain, as they underlie means of human communication such as music and speech. Although recent studies suggest comparable mechanisms for synchronizing with periodically moving visual objects, the extent to which it applies to ecologically relevant information, such as the rhythm of complex biological motion, remains unknown. The present study addressed this issue by linking rhythm of music and dance in the framework of action-perception coupling. As a previous study showed that observers perceived multiple metrical periodicities in dance movements that embodied this structure, the present study examined whether sensorimotor synchronization (SMS) to dance movements resembles what is known of auditory SMS. Participants watched a point-light figure performing two basic steps of Swing dance cyclically, in which the trunk bounced at every beat and the limbs moved at every second beat, forming two metrical periodicities. Participants tapped synchronously to the bounce of the trunk with or without the limbs moving in the stimuli (Experiment 1), or tapped synchronously to the leg movements with or without the trunk bouncing simultaneously (Experiment 2). Results showed that, while synchronization with the bounce (lower-level pulse) was not influenced by the presence or absence of limb movements (metrical accent), synchronization with the legs (beat) was improved by the presence of the bounce (metrical subdivision) across different movement types. The latter finding parallels the “subdivision benefit” often demonstrated in auditory tasks, suggesting common sensorimotor mechanisms for visual rhythms in dance and auditory rhythms in music.